2013
DOI: 10.1007/s40264-013-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Reference Set to Support Methodological Research in Drug Safety

Abstract: A reference set of test cases can be established to facilitate methodological research in drug safety. Creating a sufficient sample of drug-outcome pairs with binary classification of having no effect (negative controls) or having an increased effect (positive controls) is possible and can enable estimation of predictive accuracy through discrimination. Since the magnitude of the positive effects cannot be reliably obtained and the quality of evidence may vary across outcomes, assumptions are required to use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 74 publications
1
120
0
Order By: Relevance
“…Although actual incidence cannot be inferred from spontaneous reporting systems, the fact that antimycotics are reported in approx 3% of the total cases in FAERS suggests that the risk could be common. Our study also confirmed that miconazole and griseofulvin are not associated with clinically significant risk of DILI, a finding in line with recent data from EU-ADR and OMOP Consortia (Europe and United States projects, respectively), which labeled these drugs as "negative controls" in drug safety studies investigating DILI, based on the existing scientific literature and expert opinion [48,49] . As a matter of fact, miconazole is mainly used as topical preparation, whereas griseofulvin has specific tropism for keratin tissues with only low plasma concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Although actual incidence cannot be inferred from spontaneous reporting systems, the fact that antimycotics are reported in approx 3% of the total cases in FAERS suggests that the risk could be common. Our study also confirmed that miconazole and griseofulvin are not associated with clinically significant risk of DILI, a finding in line with recent data from EU-ADR and OMOP Consortia (Europe and United States projects, respectively), which labeled these drugs as "negative controls" in drug safety studies investigating DILI, based on the existing scientific literature and expert opinion [48,49] . As a matter of fact, miconazole is mainly used as topical preparation, whereas griseofulvin has specific tropism for keratin tissues with only low plasma concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Event frequency and other qualifiers are also extracted. SPLICER demonstrated high accuracy in AE extraction, with a sensitivity of 93% and PPV of 95%, and was used in various projects including the formation of the OMOP gold standard[49, 50] and in assessing the labeling consistency of bio-equivalent drugs[51]. While not yet publicly available, the tool as well as the resulting knowledgebase can be obtained by contacting the authors.…”
Section: Product Labelingmentioning
confidence: 99%
“…Even with only four adverse event outcomes under investigation, an extensive literature search and evaluation was required to identify the 165 drug-event pairs in which the drug was clearly implicated [10]. The search had to be repeated to document the 234 cases where no association was suspected; proving a negative is always an uncertain task because undocumented adverse effects could well exist.…”
Section: The Observational Medical Outcomes Partnership (Omop) Experimentioning
confidence: 99%